Palimpsestuous Manifestations of Slavery-Inflicted Somatic and Psychological Trauma in Toni Morrison’s Beloved (1987) - Panteleimon Tsiokos (Pivot: A Journal of Interdisciplinary Studies and Thought, 2022)
My essay explores Toni Morrison’s Beloved ability to map out the often irrepresentable consequences of slavery-inflicted trauma on the survivors’ bodies and souls. In particular, it discusses the inextricability of the physical and psychological element in the changing same of the African American condition in the U.S.A. With references to the Middle Passage, slave scar-branding, freed slaves’ infanticide and inability to escape the vortex of somatic and psychological trauma, Beloved provokes its audience to reflect on the history of racism and slavery-inflicted trauma in the U.S.A. Morrison’s fictional testimony may therefore be approached as a reparative attempt to American history by unveiling how the U.S. has always constituted a nation founded on systemic and systematic exclusion of African Americans who were continuously regarded as second-class citizens.